Five year prospective study of the incidence, clinical features, and diagnosis of achalasia in Edinburgh. Issue 8 (August 1992) - Howard, P J; Maher, L; Pryde, A; Cameron, E W; Heading, R C
Abstract : With the increasing availability of manometry, patients with achalasia are often referred at an early stage when they lack the classic features of established disease. A prospective five year study of the presenting features of untreated achalasia referred to our department was undertaken. Twenty men and 18 women presented throughout adult life, with a mean age at the time of diagnosis of 44 years (range 17 to 76 years). The presenting symptoms were dysphagia: for solids (100%) and for liquids (97%), chest pain (74%), and weight loss (60%). Endoscopy was reported as normal in 15 patients and achalasia was suggested in only 21 of 33 barium examinations. Fourteen had been treated for gastrooesophageal reflux but none had been misdiagnosed as having cardiac or psychiatric disease. The annual incidence of achalasia in the Lothian region is 0.8/100, 000 of population. Persistent dysphagia is the cardinal symptom of achalasia which presents throughout adult life. Nevertheless, recent onset achalasia is often misdiagnosed as gastrooesophageal reflux disease. Because endoscopy is frequently normal and the diagnosis is often not made by radiology, manometric investigation is necessary if the condition is to be recognised and treated at an early stage.